Determinants of pet owner's loyalty using modified SERVQUAL - Mat Ali, Emielia; Sabri, Mohamad Fazli; Mohd Nor, Norhariani; Megat Abd Rani, Puteri Azaziah; Yusof, Radduan; Wijekoon, Rusitha (Growing Science, 2021)
The objective of the current study is to explore the factors affecting customer loyalty towards service quality at veterinary clinics in Kuala Lumpur. As veterinary clinic engaged with service businesses, it is fundamental to focus on the client’s perception of their service. A modified version of SERVQUAL was used to assess the service quality of the veterinary clinics. The total number of 200 respondents conveniently selected in this study, and the pre-tested questionnaires which contains five segments; demographic profile of the respondent, the expectations and perceptions of clients about the service quality of the veterinary clinic, client satisfaction, and loyalty respectively were randomly circulated. The service quality dimensions investigated in the research were tangible, reliability, responsiveness, assurance, empathy, accessible, animal welfare, and pricing. The collected data were analyzed using SPSS software, and tabulated as descriptive, correlation, and regression analysis. All the dimensions which were used are significantly correlated with each other. The service quality dimensions; tangible, responsiveness, assurance, empathy, accessible, animal welfare were the key antecedents of the customer loyalty. Thus, in order to maintain competitive in business, the veterinary clinics should improve their quality of service with the aim of attract new customers, and maintain the business as profitable manner.